A novel dual-glucagon-like peptide-1 and glucose-dependent insulinotropic polypeptide receptor agonist is neuroprotective in transient focal cerebral ischemia in the rat. Issue 1 (6th January 2016) - Han, Ling; Hölscher, Christian; Xue, Guo-Fang; Li, Guanglai; Li, Dongfang
Abstract : Glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) receptor agonists have been shown to be neuroprotective in previous studies in animal models of Alzheimer's or Parkinson's disease. Recently, novel dual-GLP-1/GIP receptor agonists that activate both receptors (DA) were developed to treat diabetes. We tested the protective effects of a novel potent DA against middle cerebral artery occlusion injury in rats and compared it with a potent GLP-1 analog, Val(8)-GLP-1(glu-PAL). Animals were evaluated for neurologic deficit score, infarct volume, and immunohistochemical analyses of the brain at several time points after ischemia. The Val(8)-GLP-1(glu-PAL)-treated and DA-treated groups showed significantly reduced scores of neurological dysfunction, cerebral infarction size, and percentage of TUNEL-positive apoptotic neurons. Furthermore, the expression of the apoptosis marker Bax, the inflammation marker iNOS, and the survival marker Bcl-2 was significantly increased. The DA-treated group was better protected against neurodegeneration than the Val(8)-GLP-1(glu-PAL) group, and the scores of neurological dysfunction, cerebral infarction size, and expression of Bcl-2 were higher, whereas the percentage of TUNEL-positive neurons and the levels of Bax and iNOS were lower in the DA group. DA treatment reduced the infarct volume and improved the functional deficit. It also suppressed the inflammatory response and cell apoptosis after reperfusion. In conclusion, the novel GIP and GLP-1 dual-receptor agonist is more neuroprotective than a GLP-1 receptor agonist in key biomarkers of neuronal degeneration.